1998
DOI: 10.12938/bifidus1996.17.1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Probiotics and Biotherapeutic Agents in Humans

Abstract: Probiotics or biotherapeutic agents can influence physiology through direct or indirect effects occurring in the gastrointestinal tract. Knowledge on their pharmacokinetics is needed 1) to answer the questions how much probiotic should be consumed?, how often?, how long?; 2) to correlate the effects with the concentration of the probiotic at the target site; 3) to validate hypotheses such as "a probiotic should be of human origin, ... have a high survival capacity, ... adhere to the intestinal epithelium" ...;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…It did not colonize the gut, but persisted throughout the 1‐week period of administration. Studies assessing the survival of ingested microorganisms in the gastrointestinal tract are important in the development of oral vaccines or probiotics 6 . Comparisons of strains may sometimes be difficult because of slight differences in the recovery from the chyme, which may be partly influenced by culture techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It did not colonize the gut, but persisted throughout the 1‐week period of administration. Studies assessing the survival of ingested microorganisms in the gastrointestinal tract are important in the development of oral vaccines or probiotics 6 . Comparisons of strains may sometimes be difficult because of slight differences in the recovery from the chyme, which may be partly influenced by culture techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Peyer’s patches, which are mainly located in the terminal ileum. Few lactic acid bacteria strains have been studied for their pharmacokinetics in the gastrointestinal tract, which is known to vary from strain to strain 6 . In vitro techniques have been proposed for this purpose, 7 –9 but the most relevant information is that obtained in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…As a constraint, the pulse signal should be above the detection level to quantify the viability of the bacteria ingested within the host. In general, most of probiotic bacteria are excreted after ingestion (Marteau and Vesa 1998). The indigenous gastrointestinal microbiota acts as an integral defense against the colonization of orally introduced microbes.…”
Section: Discussionmentioning
confidence: 99%
“…A pharmacological approach was used to assess the positive effects and potential side effects of the products as well as their pharmacokinetics (2,4). The level of evidence for efficacy can be assessed with the rules of evidence-based medicine.…”
mentioning
confidence: 99%
“…The level of evidence for efficacy can be assessed with the rules of evidence-based medicine. We now know that the stability of many products (but not all) is good (5), that many strains (but not all) survive in the gastrointestinal tract (4), and that many double-blind randomized controlled trials (RCT) reported that some probiotics were more efficient than a placebo or a control treatment in specific clinical situations. The effects can be direct or indirect through modulation of the endogenous flora or of the immune system (2).…”
mentioning
confidence: 99%